Pengaruh Religiositas, Altruisme dan Literasi Zakat Terhadap Keputusan Membayar Zakat dengan Kesadaran Sebagai Variabel Intervening - Irvan Widi Santoso; Dede Nurohman; Muhammad Aswad (Ikatan Da'i Indonesia, 2025)
Indonesia, with its predominantly Muslim population, holds substantial potential for zakat as a source of social financing, estimated at IDR 327 trillion. However, actual zakat collection remains low, reaching only about 4.3% of this potential. Despite increasing collection trends—even during the pandemic—public reluctance to channel zakat through official institutions persists. This study investigates the influence of religiosity, altruism, and zakat literacy on zakat payment decisions, with awareness as a mediating variable. Employing a quantitative approach, primary data were collected from 344 employees of KPP Pratama in the former Kediri Residency area using probability sampling. Path analysis was conducted with SmartPLS 4. The findings reveal that religiosity, altruism, and zakat literacy significantly and positively affect zakat payment decisions, both directly and indirectly through awareness. Among these, altruism exhibited the weakest influence, indicating the need for greater attention from policymakers and zakat institutions. These results underscore the importance of integrating ethical and religious values to support sustainable economic development.